2013
DOI: 10.4414/smw.2013.13744
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and neutrophil gelatinase-associated lipocalin: biomarkers for acute kidney injury after congenital heart surgery

Abstract: In patients after congenital heart surgery, urine NGAL indicates the damaging force of cardiopulmonary bypass and serum Cystatin C is a valuable predictive biomarker for resulting acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 22 publications
1
28
2
1
Order By: Relevance
“…Previous studies in the recent literature have evaluated serum Cys C as an early marker of AKI, as well as its severity, in children sustaining AKI secondary to CPB . They have shown that it is a good marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in the recent literature have evaluated serum Cys C as an early marker of AKI, as well as its severity, in children sustaining AKI secondary to CPB . They have shown that it is a good marker.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that serum Cys C can be used as an early biomarker of AKI resulting from CPB . Multiple studies have evaluated its performance in comparison with serum Cr . A potential limitation of these studies is that they define AKI based on increase in serum Cr or decrease in Cr‐based GFR measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative cystatin C level also independently predicted longer duration of ventilation and intensive care unit stay [46]. Other recent reports have provided confirmatory results, albeit with a slightly reduced AUC of 0.71–0.81 [4749]. A recent multicenter prospective cohort study assessed the change in tubular injury biomarkers of AKI with changes in cystatin C in children undergoing cardiac surgery with CPB [50].…”
Section: Novel Diagnostic Strategies In Akimentioning
confidence: 98%
“…Üriner belirleyicilerden idrar sodyum içe-riği özgün ve duyarlı olmayan bir testtir. Ayrıca filtre edilen yüksek moleküler ağırlıklı proteinler ve tübüler proteinler veya enzimler de idrarda saptanabilen fakat özgün olmayan ayrıca izlem yönü olmayan üriner biyo-belirteçlerdir (31,32).…”
Section: Renal Hasar Biyo-belirteçleriunclassified